4(4x-3)+6=-3

Simple and best practice solution for 4(4x-3)+6=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(4x-3)+6=-3 equation:


Simplifying
4(4x + -3) + 6 = -3

Reorder the terms:
4(-3 + 4x) + 6 = -3
(-3 * 4 + 4x * 4) + 6 = -3
(-12 + 16x) + 6 = -3

Reorder the terms:
-12 + 6 + 16x = -3

Combine like terms: -12 + 6 = -6
-6 + 16x = -3

Solving
-6 + 16x = -3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 16x = -3 + 6

Combine like terms: -6 + 6 = 0
0 + 16x = -3 + 6
16x = -3 + 6

Combine like terms: -3 + 6 = 3
16x = 3

Divide each side by '16'.
x = 0.1875

Simplifying
x = 0.1875

See similar equations:

| 3x+2(5x+9)1=35 | | -7=5+3a-6a | | 72x^4-50x^2=0 | | -18=-2n-4n | | 10x+-3=4x-21 | | 11x-3(6-3x)= | | 3x+4(3x-5)=130 | | 3.98i+11.94=23.88 | | 3x+15=2x-5 | | 8-(6-7)=0 | | 8(x+4)=-64 | | 3y+2y=2y-5x | | X+m=no+rq | | 7x-32-9x=8 | | Y=3x^5+3x^3-60x | | -6-(6-6p)=0 | | 4(4-4x)+4=-2x+2-14x | | 5-9+x=65 | | -4=4(3-b) | | 6x+3(4x+2)=96 | | -4x+6=6x+16 | | 9x-1=2x-12 | | -14=3x+10 | | 3x*-5=4x*-2 | | 10+x-6=2 | | 3h-6=24 | | 6i-4=2i+24 | | 15x+3x-4=14whatisx | | 3x+5x+5=11+10x+6 | | 6(x+3)+7-x=4x(x+3) | | S-15=15.19 | | 8X-14=7X+9 |

Equations solver categories